The complete mitochondrial genome of Arhopalus oberthuri Hua, 2002 (Coleoptera: Spondylidinae) - Xufei Pan; Xiaohong Han; Yukun Zhu; Yunfei Liu; Zengzeng Shi; Shi Chen; Songqing Wu; Yinghua Tong (Mitochondrial DNA. Part B. Resources, 2022)
Arhopalus oberthuri is a pest which spreads in China, Laos, Japan and some other countries in Asia. The complete mitochondrial genome of A. oberthuri is 15,854 bp in length with 32.1% GC content, including 38.2% A, 20.4% C, 11.7% G, 29.7% T. There are 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA) and two ribosomal RNA genes (rRNA) encoded in the genome. The graph of phylogenetic analysis gives the information that Arhopalus oberthuri is closer to Arhopalus unicolor. This study provided a scientific basis for the population genetics, phylogeny, and molecular taxonomy of A. oberthuri.